Errors in Students’ Writing (Reports from ProWritingAid) - Masitha Rahma; Evynurul Laily Zen (Scope : Journal of English Language Teaching, 2023)
This research aims to find out the types of students’ writing errors which are detected and not by ProWritingAid, a language checker software.  This was a qualitative study using a document analysis method with ProWritingAid being the primary language learning instrument to analyze. To collect the data, 18 pieces of students’ writing carried out as the experimental task for this research was focused on writing personal letter. These writings were checked in the software, and manually rechecked by the researcher afterward. The results showed that ProWritingAid was able to detect 21 types of writing errors including missing pronoun, preposition, and determiner. Meanwhile, there were also undetected errors found, for example, unnecessary capitalization and missing punctuation. In conclusion, while ProWritingAid can help students to analyze their errors. However, human analysis is still needed due to the undetected errors.